Bacteriological profile and antibiotic susceptibility of neonatal sepsis in neonatal intensive care unit of a tertiary hospital in Nepal - Bhishma Pokhrel; Tapendra Koirala; Ganesh Shah; Suchita Joshi; Pinky Baral (BMC, 2018)
Abstract Background Neonatal sepsis, one of the leading causes of mortality in neonatal intensive care units (NICU) of developing countries like Nepal, is often not extensively studied. In order to decrease the morbidity and mortality associated with neonatal sepsis, neonatologists should have a keen knowledge of the existing bacteriological flora and their antibiotic susceptibility pattern. In this study, we aim to determine the bacteriological profile and antibiotic susceptibility pattern of culture positive neonatal sepsis in the NICU of a tertiary teaching hospital in Nepal. Methods This was a retrospective cross-sectional study of all blood culture positive sepsis cases among neonates admitted to the neonatal intensive care unit of Patan Hospital, Nepal between April 15, 2014 and April 15, 2017. All neonates with a clinical suspicion of sepsis with a positive blood culture were identified. Patient demographics, clinical details, maternal risk factors, and laboratory data including bacteriological profiles and antimicrobial susceptibilities were recorded and analyzed. Results Of the 336 neonates admitted in the NICU, 69 (20.5%) had culture-positive sepsis. The majority were early-onset sepsis (n = 54, 78.3%) and were among the preterm babies (n = 47, 68.1%). Most bacterial isolates were gram-negative, predominantly the Klebsiella species (n = 23, 33.3%). Klebsiella showed high resistance to commonly used antibiotics such as; Cefotaxime (90.5%), Gentamicin (75%), Ciprofloxacin (76.2%), Ofloxacin (72.2%) and Chloramphenicol (65%). However, they showed good susceptibility to Carbapenems (100%), Colistin (88.8%) and Tigecycline (81.8%). Among cultures with gram-positive species, Coagulase-negative Staphylococci (CONS) (n = 14, 20.3%) predominated. CONS showed high resistance to Oxacillin (80%), Cefotaxime (66.7%) and Meropenem (80%) but good susceptibility (100%) to Vancomycin and Linezolid. Prevalence of multidrug-resistant strain was 73.9%. Conclusions Klebsiella species and CONS were the most common causes of neonatal sepsis in our study. A significant proportion of the isolates were multidrug resistant strains, which pose a great threat to neonatal survival, and thereby, warrant modification of existing empirical therapy. Implementation of effective preventive strategies to combat the emergence of antibiotic resistance is urgently needed. We recommend a combination of Piperacillin-Tazobactam and Ofloxacin as the first line therapy and combination of Vancomycin and Meropenem as the second line empirical therapy in our NICU.